2013
DOI: 10.1016/j.mbs.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the response of a biofilm to silver-based antimicrobial

Abstract: Biofilms are found within the lungs of patients with chronic pulmonary infections, in particular patients with cystic fibrosis, and are the major cause of morbidity and mortality for these patients. The work presented here is part of a large interdisciplinary effort to develop an effective drug delivery system and treatment strategy to kill biofilms growing in the lung. The treatment strategy exploits silver-based antimicrobials, in particular, silver carbene complexes (SCC). This manuscript presents a mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…The addition of fluid flow over the biofilm as a mechanism for nutrient and SCC transport represents an extension of Stine et al (2012). Stine et al (2012) showed that 10 9 particles per ml of biofilm is able to surpass the MIC in a Bacillus anthracis biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The addition of fluid flow over the biofilm as a mechanism for nutrient and SCC transport represents an extension of Stine et al (2012). Stine et al (2012) showed that 10 9 particles per ml of biofilm is able to surpass the MIC in a Bacillus anthracis biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Stine et al (2012) showed that 10 9 particles per ml of biofilm is able to surpass the MIC in a Bacillus anthracis biofilm. This particle density is similar to that used in the model presented here, but is shown to effectively treat a biofilm with an MIC 10 times higher than that of P. aeruginosa used here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As well-known examples of the thread that biological films represent to human health, we may cite the recognition of the colonization of some bacterial colonies in chronic wounds [22], the persistence of certain bacterial infections associated with foreign bodies due to the formation of biological films [18], the growth of infectious microbial colonies in endourological devices [34], just to mention some health-related conditions derived from the growth of biological colonies. It is worth mentioning that many other realistic problems also involve the investigation of biological films, such as the biological treatment of polluted fluids [3,4,13,20], the development of microbial fuel cells to generate electrical power [19,24,25,37], the design of biological sensors [5,35], among other applications [32].…”
Section: Introductionmentioning
confidence: 99%